2018
DOI: 10.1111/echo.14016
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular morphology and function in athletes with elevated pulmonary systolic arterial pressure

Abstract: Pulmonary arterial systolic pressure elevation in young athletes is associated with pronounced right ventricular enlargement, even when compared to matched athletes. Conventional and speckle tracking echocardiography showed preserved right ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…2C), suggesting that the greater relative heart mass is a basis for the difference in left ventricle stroke volume between the groups. Stroke volume is correlated with cardiac mass in birds (Grubb, 1983;Seymour and Blaylock, 2000) and trained human athletes (Mirea et al, 2018). If increased cardiac mass in the hypoxicincubated alligators in this study translates to a relatively larger ventricle lumen volume, then this could account for the increased baseline stroke volume in the hypoxic group.…”
Section: Response To Dobutaminementioning
confidence: 67%
“…2C), suggesting that the greater relative heart mass is a basis for the difference in left ventricle stroke volume between the groups. Stroke volume is correlated with cardiac mass in birds (Grubb, 1983;Seymour and Blaylock, 2000) and trained human athletes (Mirea et al, 2018). If increased cardiac mass in the hypoxicincubated alligators in this study translates to a relatively larger ventricle lumen volume, then this could account for the increased baseline stroke volume in the hypoxic group.…”
Section: Response To Dobutaminementioning
confidence: 67%
“…In the multiple logistic regression model, the enhanced LV diastolic function in elite endurance athletes was due to a reduced resting heart rate, ( 29 ) and that in elite strength athletes might be related to an improved LV compliance. The reduced heart rate related to endurance exercise has been associated with an increase of parasympathetic tone ( 30 ). On the contrary, physically active Asian males regardless of endurance or strength exercise in the present study had a similar RVSP (25–29 mmHg) compared to non-Asian endurance athletes (26–27 mmHg), which was higher than that in sedentary controls in prior studies (16–22 mmHg) ( 25 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated systolic pulmonary artery pressure (sPAP) may be induced by strenuous endurance exercise. Mirea et al [24] found that 12.9% of the athletes they studied exhibited higher sPAP, which was further enhanced by bicycle ergometric stress effort and correlated with significant RV enlargement. Despite this, both conventional methods and STE indicated preserved RV function in these athletes.…”
Section: Athlete's Heart Grey Zonementioning
confidence: 91%